PHARMACOLOGY EFFECT OF CARDIOVASCULAR DRUGS ON THE LEVEL OF THYROID HORMONES AND VITAMIN-D. - Painuly, Neelam; Sharma, Amit (Asian Journal of Pharmaceutical Research and Development, 2018)
Cardiovascular system is an important system of body. This consists the heart and blood vessels. Any kind of heart disease is dangerous. Thyroid hormone is one of the leading hormones which is involving in the cardiovascular mechanism. Any disturbance in the balance of hormone can cause serious problems which may be dangerous to cardiovascular system. So it balance should be maintained properly. Various treatment related to this are found but they may cause various alteration in the production of thyroid hormone. So in order to give proper treatment to patient all the aspects should be checked and observed properly considering the health of patient. Amlodipine, Propranolol, Captopril, Amiodarone are some of the medicines used in the treatment of these diseases. Knowledge of drug should be proper so that any risk of thyroid abnormalities can be minimized and diagnosed in proper time. Key words: Arrhythmia, cardiovascular, vitamin D, Amlodipine, Propranolol, Captopril, Amiodarone